Sacredness of the Family in Cultural Practices of Northern PreAzov Peoples: Historical and Theoretical Aspects - L. Moskalyova; L. Eremina (University of Sofia, 2015)
The article presents the materials based on the analysis of the family in cultural practices of Northern PreAzov peoples. There one can find description of cultural traditions, rituals and beliefs of the peoples of Northern PreAzov region. A special place is the description of ancient customs that are associated with the problems of family education of children of various nationalities.